Canadian journal of occupational therapy. (Ottawa : CAOT)
The mission of the journal is to provide a forum for leading-edge occupational therapy scholarship that advances theory, practice, research, and policy. The vision is to be a high-quality scholarly journal that is at the forefront of the science of occupational therapy and a destination journal for the top scholars in the field, globally. As CJOT is an English/French bilingual journal. Articles are published in the language of submission with the title, key words, and abstract translated into the other language.
Zie loginlijst LEHO - cursus Bibliotheken
Keywords: Ergotherapie